APAKAH PROGRAM PERCEPATAN PEMBANGUNAN INFRASTRUKTUR MENGURANGI TINGKAT PENGANGGURAN? - I Gede Made Artha Dharmakarja (Jurnal Anggaran dan Keuangan Negara Indonesia (AKURASI), 2021)
The Government of Indonesia has implemented a massive Infrastructure Development program since 2015. This program aims to increase economic growth and create jobs. This study intends to determine the impact of massive infrastructure development on the decline in the unemployment rate. The data sources are 32 provinces in Indonesia and the time period is 2008 - 2019. The independent variables are data on clean water infrastructure, roads, ports, and airports. Data processing using panel data regression analysis method. The results of this study conclude that the increase in infrastructure development in 2015 - 2019 simultaneously or partially, has a significant effect on decreasing the unemployment rate, compared to before the program was in 2008 - 2014. Road infrastructure development has the greatest effect on decreasing the unemployment rate.